THE RITUAL OF TRANSITION AS A FACTOR OF SOCIOCULTURAL DYNAMICS IN THE CONTEXT OF POSTMODERN SOCIETY - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article analyzes the transformation of the role of ritual in different types of society, responsible for social reproduction, maintaining community and order. The tasks are: 1) to reveal the characteristic features of the ritual of transition as a sociocultural phenomenon; 2) consider the stage of transition of the system from one state to another, associated with the loss of structure, hierarchy, status of elements; 3) characterize the transformation of the ritual of transition in the conditions of the multicultural and poly-subject sociality of the modern world. Research methods are selected due to the tasks of the research. The general methodological paradigm of the study is socio-philosophical, which allows to consider the ritual of transition as a specific social phenomenon, the forms of which depend on the types of societies, as well as to identify and demonstrate the significance and content of ritual practices in the processes of postmodern society. The comparative method is used to contrast a traditional ritual of transition with modern ritual practices of initiation. The method of historical sociology (N. Elias) in conjunction with the genealogical approach to the study of social phenomena (M. Foucault) are used to analyze transformations of ritual forms in relation to the processes of constructing and reproducing of social reality. Research results: A three-phase transition ritual involving separation, liminality and reaggregation stages is responsible for the elimination of the established social structure by adapting to the new. For a representative of a traditional society, ritual is a culturally standardized set of actions of symbolic content that are performed in situations, dictated by tradition, focused on the formation of an individual identity in the context of current sociocultural changes. The sacralized ritual of transition, within postmodern society is seen as a playful set of "schemes", "forms" of actions, no longer served as a way of social and individual harmonization in the face of many new sociocultural phenomena for the existing order. The problem of mastering a new order is actual because the liminality with the community arisen within it cannot prepare the ground for the adoption of innovations. Discussion. The most important in the study is an appeal to the anthropological and ethnographic theories of the ritual proposed by the works of E. Durkheim, E. Lich, B. Malynovskyi, M. Moss, A. Radcliffe-Brown, W. Robertson-Smith, V. Turner, J. Fraser. Modern Western studies of the problem of ritual are presented by R. Collins, M. Eliade, the concepts of the functional approach of P. Berger, P. Bourdieu, E. Giddens, K. Girce, I. Hoffmann, T. Lukman, N. Luman, G. Mead, O. Rosenstock-Hussy, R. Girard, affecting the problem of the role of rituals in everyday life in the process of constructing and reproducing social reality; the concepts of the secular ritual of D. Kertzer, S. Moore, B. Mayerhof. With all these varieties of theories and concepts of ritual, the problem associated with the analysis of ritual practices of transition in the aspect of their attitude to multicultural processes in modern society, in the above-mentioned works is not specifically addressed. Conclusion. Liminality in postmodern society becomes permanent. The prolongation of the liminal stage is due to the social uncertainty of multicultural and polysubject policy. The situation of communitas in the protracted liminal stage threatens with the emergence of a new subculture of a totalitarian nature.